2016
DOI: 10.1080/00150193.2016.1216702
|View full text |Cite
|
Sign up to set email alerts
|

Far infrared and terahertz spectroscopy of ferroelectric soft modes in thin films: A review

Abstract: Far-infrared and terahertz spectroscopy of ferroelectric soft and central modes in thin films on substrates is reviewed. In addition to classical displacive proper ferroelectrics, also incipient and relaxor ferroelectrics and multiferroics are discussed. Special attention is paid to differences between the soft-mode behavior in thin films and bulk materials (ceramics and single crystals) and their influence on the low-frequency permittivity. Particularly the effects of the thin film strains and depolarizing el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 127 publications
0
23
0
1
Order By: Relevance
“…He significantly contributed to the understanding of the nature of dipolar glasses [13,14], relaxor ferroelectrics [15][16][17][18][19] and incipient ferroelectrics [20,21]. He was the first to study ferroelectric thin films using IR spectroscopysee his review in reference [22]. In 2009, he officially retired as Head of the Department of Dielectrics, but he continues to be scientifically very active.…”
Section: Guest Editorialmentioning
confidence: 99%
“…He significantly contributed to the understanding of the nature of dipolar glasses [13,14], relaxor ferroelectrics [15][16][17][18][19] and incipient ferroelectrics [20,21]. He was the first to study ferroelectric thin films using IR spectroscopysee his review in reference [22]. In 2009, he officially retired as Head of the Department of Dielectrics, but he continues to be scientifically very active.…”
Section: Guest Editorialmentioning
confidence: 99%
“…THz spectroscopy extended significantly the knowledge in the area of ferroelectric phase transitions and ferroelectric switching. Significant contribution to this area has been made by J. Petzelt [1] who showed that THz spectroscopy is a very sensitive tool to study soft and central modes in thin films on substrates. Regarding the materials studied in this paper (BaTiO 3 ), he showed that central mode and soft mode coexist in the THz range and that the soft phonon mode softens only partially [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Анализ полученных спектров с наибольшей полнотой проведен для керамических и кристаллических объемных образцов [23]. Для тонкопленочных образцов основной акцент сделан на изучении температурной эволюции центральной (CM) и мягкой (SM) мод [39], ко-торые формируют примерно половину диэлектрической проницаемости на низких частотах (ниже 1 GHz) [1] и определяют ее температурную зависимость. Было уста-новлено, что в пленках в области средних концентраций Zr−Ti фазовый переход в сегнетоэлектрическое состо-яние размыт по температуре.…”
Section: Introductionunclassified